2012
DOI: 10.1016/j.jpsychires.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Sleep promotes consolidation and generalization of extinction learning in simulated exposure therapy for spider fear

Abstract: Simulated exposure therapy for spider phobia served as a clinically naturalistic model to study effects of sleep on extinction. Spider-fearing, young adult women (N=66), instrumented for skin conductance response (SCR), heart rate acceleration (HRA) and corrugator electromyography (EMG), viewed 14 identical 1-min videos of a behaving spider before a 12-hr delay containing a normal night’s Sleep (N=20) or continuous daytime Wake (N=23), or a 2-hr delay of continuous wake in the Morning (N=11) or Evening (N=12).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 48 publications
4
106
0
1
Order By: Relevance
“…From the clinical view, it is important that fear extinction generalizes so that the individuals can be less reactive to the fearful stimuli encountered outside of therapy (Rowe & Craske, 1998;Vansteeenwegen et al, 2007). Although preliminary studies (Pace-Schott et al, 2012;Kleim et al, 2014) …”
Section: Effects Of Sleep After Different Types Of Exposure Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…From the clinical view, it is important that fear extinction generalizes so that the individuals can be less reactive to the fearful stimuli encountered outside of therapy (Rowe & Craske, 1998;Vansteeenwegen et al, 2007). Although preliminary studies (Pace-Schott et al, 2012;Kleim et al, 2014) …”
Section: Effects Of Sleep After Different Types Of Exposure Therapymentioning
confidence: 99%
“…Studies have found that sleep strengthens the consolidation of memories, regulation of emotional memories, stabilization of memories, and fear extinction (Rasch & Born, 2013;Pace-Schott, Verga, Bennett, & Spencer, 2012;Walker, 2008;Spoormaker et al 2012). Specifically, sleep participates in improving synaptic and systems consolidation, the storing of newly encoded information into memory, which are major processes of memory consolidation (Maquet, 2001).…”
Section: Effects Of Sleep On Memorymentioning
confidence: 99%
“…The finding that expectancy violation was a significant mediator for kcal intake is interesting and in line with previous research , suggesting that that the violation of expectancies indeed is an important target for cue exposure sessions, though it's causal role needs to be investigated in experimental designs that manipulate expectancy violation. And although good sleep has shown to be important for consolidation of new CS-noUS memories (e.g., Pace-Schott et al, 2012;Spoormaker et al, 2012), sleep quality did not influence or moderate treatment outcome.…”
Section: Discussionmentioning
confidence: 87%
“…However, no generalisation to non-exposed foods was found. Generalisation of the exposure effect remains very important for the usability of exposure in clinical practice; it is plausible that more sessions are required for generalisation to occur, and/or better consolidation of the new CS-noUS memory, for example by sleeping after the session (Pace-Schott, Verga, Bennett, & Spencer, 2012). Further, even when the new CS-noUS association has been wellconsolidated, the original CS-US association remains intact and forms a risk of return of responses in another context or later in time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation